Displacement and Violation of Inalienable Rights in Alan Gratz’s Refugee - Marasini, Bishnu (KMC Research Journal, 2022)
Refugees are human beings but not citizens of the nation; they are left in no man's land and treated as traitor, criminal and animal. Even though, human rights about refugees are penned in different charter, such rights are not implemented appropriately. They leave their nation longing for survival; however many countries do not let them to enter their territory. Their right in home country is absconded and their identity of being citizen is confiscated and they are left to live the bare life. Those who are lucky to flee from the home have to face grave troubles and violence from police, and the state rules and regulations violating the International Human Rights of right to live the dignified life. This article analyzes the solemn issues from the perspective of Derrida, Kant, and Hannah Ardent, who explicitly urges about the rights of refugee and their survivals in Alan Gratz novel Refugee.